Long-term follow up of interventional therapy of secundum atrial septal defect - Yuan, Yi-Qiang; Huang, Qiong; Yu, Li; Wang, Rui-Min; Zhao, Yu-Jie; Guo, Ying-Xian; Sun, Jun-Hua; Niu, Si-Quan; Sun, Yun; Yang, Xing-Ming; Mao, You-Lin (Chinese medical journal, 2012)
Background The percutaneous transcatheter closure of secundum atrial septal defect （ASD） is increasingly a widespread alternative to surgical closure.The aim of this study was to assess long-term results of percutaneous closure of secundum-type atrial septal defect （ASD Ⅱ）.Methods Between January 2001 and December 2005,61 patients underwent a successful percutaneous closure of ASD Ⅱ; including 25 male and 36 female.All were included in the patient study and were followed up to monitor by electrocardiogram and echocardiography,at intervals of 3 days,3 months,6 months,1 year,2 years,and 5 years after operation.Results Three days after percutaneous transcatheter septal closure （PTSC）,the right atrium diameter,right ventricular end-diastolic left-right diameter and right ventricutar end-diastolic volume （RVEDV） decreased significantly （P 〈0.05）.Right ventricular end-diastolic anteroposterior diameter （RVEDD）,right ventricular end-systolic volume （RVESV） and right ventricular ejection fraction （RVEF） also decreased （P〈0.01）.During the period from 3 to 6 months,the size of the right atrium and right ventricle returned to normal range.Three days after PTSC,the left ventricular end-diastolic diameter （LVEDD）,left ventricular end-diastolic volume （LVEDV）,left ventricular end-systolic volume （LVESV）,left ventricular-systolic volume （LVSV） and left ventricular ejection fraction （LVEF） were significantly increased （P 〈0.05）.At 1 year,the size of the left atrium,left ventricle and left cardiac function returned to normal range （P 〈0.01）.There were no deaths or significant complications during the study.At five year follow-up,all defects were completely closed and remained closed thereafter.Conclusion Transcatheter closure of ASD Ⅱ effectively eliminated the abnormal shunt and,subsequently improved the dimensions of each chamber and cardiac function.